Growth and Development of Ovarian Tissue Grafts After Applying Various Freeze-Thawing Protocols - Trutaieva, Iryna A.; Kiroshka, Victoria V.; Gurina, Tatuyana M.; Bondarenko, Tatuyana P. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):160.